The Manhattan gambit - Stein, Benjamin (New York : Doubleday & Company, Inc., 1983)
The novel is set in an over confident USA in 1943. Nobody takes the Nazi prisoners very seriously, either at Fort Ord, CA, or the public at large The American government knows about the Nazi mass murders, but is keeping that knowledge very quiet. The heroes are John Quinn, a detective who who is trudging through life. His wife left him for another man, and he hardly coping. Alice Burton, a female layer, is brilliant but men consider " mousy ". They are after an escaped Nazi soldier. He is on some big mission, object and location unknown. Both are on their own, in an unaware America.
Keywords: SPY STORIES